Mongolia : Joint IMF/World Bank Debt Sustainability Analysis Under the Debt Sustainability Framework for Low-Income Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper focuses on the increase in the external debt stock that reflects donor financing, including IMF and Bank lending to help Mongolia smooth its fiscal adjustment path after the major terms of trade shock. The fiscal deficit is expected to steadily decline until revenues from the Oyu Tolgoi mine enter the budget. Since the World Bank's 2008 Debt Management Performance Assessment (DeMPA), Mongolia has improved debt management procedures and has prepared a medium-term debt management strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet